Water-based varnish as well as preparation method and application thereof
Through specific component ratios and process treatments, high-permeability water-based semi-matte varnish is prepared, which solves the problem of insufficient permeability of water-based varnish and significantly improves the permeability and thermal transfer effect of the coating film.
Patent Information
- Application Number
- CN202411472635.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-22
AI Technical Summary
The water-based semi-matte varnish is not as permeable as the solvent-based varnish during use, resulting in a confusing appearance of the coating and affecting the thermal transfer printing pattern effect.
Components with specific mass ratios, including aqueous acrylic resins, amino resins, unsurface-treated silica matte powders, aqueous nonionic dispersants and polyether modified silicone levelers, through high-speed dispersion and low-speed mixing Process to prepare high permeability water-based varnish.
It realizes high permeability of water-based varnish, avoids the problems of glossy and whitening of the coating film, improves the effect of thermal transfer printing patterns, and is suitable for the coating of iron doors and other building materials.
Smart Images

Figure BDA0005095106370000061 
Figure BDA0005095106370000071 
Figure BDA0005095106370000072
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of industrial coatings, and in particular relates to a water-based varnish and a preparation method and application thereof. Background Art
[0002] The varnish used in the home security door and iron door industry is generally in a semi-matte state, with a glossiness of 30 to 50GU at a 60° angle. This semi-matte state will not produce strong light reflection, nor will it produce serious light pollution under strong light, which helps to relieve visual fatigue. With the strengthening of environmental protection trends and based on production safety considerations, iron door semi-matte varnish (including copper-bottom brushed varnish for security doors) has gradually transformed to water-based. During the use of water-based semi-matte varnish, it was found that compared with solvent-based semi-matte varnish, water-based semi-matte varnish is not as permeable as solvent-based varnish, resulting in a slightly hazy appearance of the coating film, which in turn affects the thermal transfer pattern effect. Summary of the invention
[0003] In order to overcome at least one of the problems existing in the above-mentioned prior art, one of the objects of the present invention is to provide a water-based varnish which can achieve a transparent effect comparable to that of a solvent-based varnish.
[0004] A second object of the present invention is to provide a method for preparing the above-mentioned water-based varnish.
[0005] A third object of the present invention is to provide an application of the above-mentioned water-based varnish.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] The first aspect of the present invention provides a water-based varnish, comprising the following components in parts by weight: 35-50 parts of water-based acrylic resin, 10-20 parts of amino resin, 1-3 parts of matte powder, 0.5-2 parts of water-based nonionic dispersant, 0.1-1 parts of polyether-modified organic silicon leveling agent, 10-25 parts of auxiliary agent, and 10-30 parts of water;
[0008] The number average molecular weight of the waterborne acrylic resin is 1500-3500 g / mol; the hydroxyl value of the waterborne acrylic resin is 80-110 mgKOH / g; and the matte powder is selected from unsurface-treated silicon dioxide.
[0009] Preferably, the water-based varnish comprises the following components in parts by mass: 38 to 48 parts of water-based acrylic resin, 11 to 18 parts of amino resin, 1.2 to 2.8 parts of matte powder, 0.8 to 1.8 parts of water-based nonionic dispersant, 0.2 to 0.8 parts of polyether-modified silicone leveling agent, 12 to 22 parts of additives, and 12 to 28 parts of water.
[0010] Further preferably, the water-based varnish comprises the following components in parts by mass: 40-45 parts of water-based acrylic resin, 12-16 parts of amino resin, 1.5-2.5 parts of matte powder, 1-1.5 parts of water-based non-ionic dispersant, 0.3-0.5 parts of polyether-modified silicone leveling agent, 15-20 parts of additives, and 15-25 parts of water.
[0011] Preferably, the number average molecular weight of the waterborne acrylic resin is 1800 to 3200 g / mol; more preferably 2000 to 3000 g / mol.
[0012] Preferably, the hydroxyl value of the waterborne acrylic resin is 85 to 105 mgKOH / g; more preferably, it is 90 to 100 mgKOH / g.
[0013] In some specific embodiments of the present invention, the water-based acrylic resin includes at least one of R1385, R1389 or R1393.
[0014] Preferably, the amino resin is selected from partially methylated amino resin; the degree of etherification of the partially methylated amino resin is 40 to 60%; more preferably 45 to 55%.
[0015] In some specific embodiments of the present invention, the partially methylated amino resin includes at least one of allnex cytec325, ineos resimene 717 or mitsuki SM5717.
[0016] Preferably, the matte powder is selected from precipitated silica without surface treatment.
[0017] In some specific embodiments of the present invention, the matte powder includes at least one of Degussa OK412, Degussa OK500, Hongsheng 230L or Hongsheng 560N.
[0018] Preferably, the aqueous nonionic dispersant includes polyethylene glycol-type polyol, polyethyleneimine compound or a combination thereof.
[0019] In some specific embodiments of the present invention, the aqueous nonionic dispersant includes at least one of Shenzhu SN-1729, Longhai LH-120 or Dow CF-10.
[0020] Preferably, the polyether-modified silicone leveling agent includes ethylene oxide polyether-modified silicone, propylene oxide polyether-modified silicone or a combination thereof.
[0021] In some specific embodiments of the present invention, the polyether-modified organic silicon leveling agent includes at least one of Shenzhu SN-4341, BYK333 or Glide 432.
[0022] Preferably, the auxiliary agent includes at least one of an amine neutralizer, a film-forming cosolvent, a wetting agent, a defoamer or an adhesion promoter; further preferably, the auxiliary agent includes an amine neutralizer, a film-forming cosolvent, a wetting agent, a defoamer and an adhesion promoter.
[0023] Preferably, the auxiliary agent includes, by weight: 1 to 3 parts of an amine neutralizer, 10 to 20 parts of a film-forming cosolvent, 0.1 to 1 part of a wetting agent, 0.1 to 1 part of a defoaming agent, and 0.1 to 1.5 parts of an adhesion promoter.
[0024] Further preferably, the auxiliary agent includes, by weight: 1.5 to 2.8 parts of amine neutralizer, 12 to 18 parts of film-forming cosolvent, 0.2 to 0.7 parts of wetting agent, 0.2 to 0.7 parts of defoaming agent, and 0.3 to 1.2 parts of adhesion promoter.
[0025] More preferably, the additives include, by weight: 2 to 2.5 parts of an amine neutralizer, 13 to 17 parts of a film-forming cosolvent, 0.3 to 0.5 parts of a wetting agent, 0.3 to 0.5 parts of a defoaming agent, and 0.5 to 1 parts of an adhesion promoter.
[0026] Preferably, the water-based varnish comprises the following components in parts by mass: 35 to 50 parts of water-based acrylic resin, 10 to 20 parts of amino resin, 1 to 3 parts of matte powder, 0.5 to 2 parts of water-based non-ionic dispersant, 0.1 to 1 part of polyether-modified silicone leveling agent, 1 to 3 parts of amine neutralizer, 10 to 20 parts of film-forming co-solvent, 0.1 to 1 part of wetting agent, 0.1 to 1 part of defoaming agent, 0.1 to 1.5 parts of adhesion promoter, and 10 to 30 parts of water.
[0027] Further preferably, the water-based varnish comprises the following components in parts by mass: 38 to 48 parts of water-based acrylic resin, 11 to 18 parts of amino resin, 1.2 to 2.8 parts of matte powder, 0.8 to 1.8 parts of water-based non-ionic dispersant, 0.2 to 0.8 parts of polyether-modified silicone leveling agent, 1.5 to 2.8 parts of amine neutralizer, 12 to 18 parts of film-forming co-solvent, 0.2 to 0.7 parts of wetting agent, 0.2 to 0.7 parts of defoaming agent, 0.3 to 1.2 parts of adhesion promoter, and 12 to 28 parts of water.
[0028] Further preferably, the water-based varnish comprises the following components in parts by mass: 40 to 45 parts of water-based acrylic resin, 12 to 16 parts of amino resin, 1.5 to 2.5 parts of matte powder, 1 to 1.5 parts of water-based non-ionic dispersant, 0.3 to 0.5 parts of polyether-modified silicone leveling agent, 2 to 2.5 parts of amine neutralizer, 13 to 17 parts of film-forming co-solvent, 0.3 to 0.5 parts of wetting agent, 0.3 to 0.5 parts of defoaming agent, 0.5 to 1 parts of adhesion promoter, and 15 to 25 parts of water.
[0029] Preferably, the amine neutralizing agent includes at least one of aqueous ammonia, N,N-dimethylethanolamine, triethylamine or triethanolamine.
[0030] Preferably, the film-forming co-solvent includes at least one of ethylene glycol butyl ether, propylene glycol methyl ether or diethylene glycol butyl ether.
[0031] Preferably, the wetting agent comprises at least one of an acetylenic glycol compound, a modified polysiloxane, a nonionic surfactant or a fluorine-containing surfactant.
[0032] In some specific embodiments of the present invention, the wetting agent includes at least one of Wet 270, BYK349, 104E or TWIN4100.
[0033] Preferably, the defoaming agent includes at least one of polydimethylsiloxane, mineral oil or acrylate defoaming agent.
[0034] In some specific embodiments of the present invention, the defoaming agent includes at least one of BYK028, AD01 or TEGO425.
[0035] Preferably, the adhesion promoter includes at least one of an epoxy phosphate adhesive, a titanate adhesive or a high molecular weight polyester adhesive.
[0036] The second aspect of the present invention provides a method for preparing the water-based varnish described in the first aspect of the present invention, comprising the following steps: blending a water-based acrylic resin, an amino resin, a matte powder, a water-based non-ionic dispersant, a polyether-modified silicone leveling agent and an additive, dispersing the mixture at a high speed, and finally adding water for low-speed mixing to obtain the water-based varnish; the rotation speed of the high-speed dispersion is greater than the rotation speed of the low-speed mixing.
[0037] Preferably, the rotation speed of the high-speed dispersion is 1000-1500 r / min.
[0038] Preferably, the high-speed dispersion time is 25 to 30 minutes.
[0039] In some specific embodiments of the present invention, the high-speed dispersion is performed until the fineness of the blend is ≤15 μm.
[0040] Preferably, the rotation speed of the low-speed mixing is 500-800 r / min.
[0041] Preferably, the low-speed mixing time is 5 to 10 minutes.
[0042] The third aspect of the present invention provides a coating, which is made from the water-based varnish described in the first aspect of the present invention.
[0043] Preferably, the 60° angle glossiness of the coating is 30 to 50 GU; more preferably, it is 35 to 48 GU.
[0044] In some specific embodiments of the present invention, the coating is a thermal transfer coating for an iron door; further, the thermal transfer coating for an iron door is prepared by the following method: the water-based varnish is applied to an iron door and treated with a thermal transfer process to obtain the thermal transfer coating for an iron door.
[0045] By using the water-based varnish provided by the present invention, various exquisite patterns and colors can be transferred to the surface of the iron door, adding an artistic atmosphere and individual characteristics to the iron door. At the same time, the thermal transfer coating also has the characteristics of high adhesion, good wear resistance, strong weather resistance, etc., which can protect the surface of the iron door from damage and extend the service life of the iron door.
[0046] The fourth aspect of the present invention provides a use of the water-based varnish described in the first aspect of the present invention in building material coating, furniture coating or interior decoration.
[0047] In some specific embodiments of the present invention, the building material coating includes door coating, wall coating, etc.; the door coating can be a wooden door, an iron door, etc., and is particularly suitable for an iron door.
[0048] The beneficial effects of the present invention are as follows: the present invention adopts a water-based acrylic resin with a specific molecular weight and hydroxyl value, combines it with an amino resin, and adopts a non-ionic dispersant to disperse the unsurface-treated silica matte powder, and adds a polyether-modified silicone leveling agent to obtain a highly permeable semi-matte water-based varnish, which solves the problems of the water-based varnish being foggy, whitish, and opaque, and has a wide range of applications in building material coatings, furniture coatings, or interior decoration, especially on the thermal transfer coating of iron doors, where a good permeability effect can be obtained.
[0049] Specifically, compared with the prior art, the present invention has the following advantages:
[0050] 1. The present invention adopts a water-based acrylic resin with a number average molecular weight of 2000-3000 g / mol and a hydroxyl value of 90-100 mgKOH / g. A high molecular weight of the resin can effectively improve the spray adaptability, improve the anti-sagging performance of the coating film, and improve the wetting and spreading of the wet film on the substrate, which is helpful to improve the adhesion; however, too high a molecular weight will lead to a high dilution ratio, reduce the construction solid content, and cause the dry film after curing to have no film thickness and poor fullness; therefore, the water-based acrylic resin within the specific molecular weight range of the present invention is selected, which has a faster surface drying, can meet the anti-sagging requirements, and can also obtain a better fullness.
[0051] 2. During the curing process of the coating, the matte powder eventually migrates to the surface of the coating to form a flat sheet due to the volatilization of the solvent in the coating and the shrinkage of the coating. Since it can scatter light and make the light scattered, it can achieve the effect of extinction. However, the surface of the matte powder is susceptible to pollution and friction damage, which affects its color and gloss. Therefore, it is particularly important to treat the surface of the matte powder to improve its stability and service life. At present, there are mainly chemical treatment, physical treatment, coating treatment and other surface treatment methods. The matte powder with surface treatment has a better feel and better suspension; while the matte powder without surface treatment has a higher cost performance, better wettability in the water-based system, and higher transparency after film formation. The present invention adds untreated matte powder so that it can be better mixed with the water-based non-ionic dispersant of the present invention during the preparation of water-based varnish to achieve a better dispersion effect.
[0052] 3. The commonly used high molecular weight hyperdispersants in water-based industrial coatings have good pigment dispersion effects, so relatively speaking, they can obtain higher gloss and stability than other types of dispersants. However, improving gloss is contrary to matte coatings and is obviously inconsistent with the formulation design principles. The water-based nonionic dispersant used in the present invention contains a pigment affinity group polymer and a surfactant (mainly polyethylene glycol type polyols and polyethyleneimine derivatives, etc.), which can reduce surface tension, has strong adsorption, can make matte powder oriented, and can relatively reduce the gloss of the coating after addition.
[0053] 4. Among the existing leveling agents, the hydroxy-terminated silicone leveling agent can react with amino groups during the curing process to provide a permanent slippery feel; the fluorocarbon-modified silicone has strong anti-shrinkage ability, good thermal stability, and can promote leveling; these two types of leveling agents are good for the feel of the coating and the wetting of the substrate, but do not play a big role in the gloss change of the coating. Acrylic leveling agents have more advantages in the final leveling dynamics, which means that the final flatness of the coating will be better than that of silicone leveling agents, and the gloss will be higher than that of other types of leveling agents, but its surface tension will be higher than that of silicone leveling agents, so the leveling dynamics are not as strong as silicone. The polyether-modified silicone leveling agent used in the present invention has improved compatibility with the resin through the polyether-modified silicone leveling agent, and has good effects in reducing surface tension and controlling surface flow. Moreover, the use of polyether-modified silicone can reduce the gloss of the coating by 30-40% under the condition of the same amount of matte powder added, and the non-ionic dispersant can reduce the gloss of the coating film more than the polymer dispersant, which means that after adding the polyether-modified silicone leveling agent and the non-ionic wetting dispersant, the combination of the two can effectively reduce the amount of matte powder in the formula, thereby improving the permeability of the coating film. DETAILED DESCRIPTION
[0054] The content of the present invention is further described in detail below through specific examples. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the principles set forth in the present invention all belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific data exemplified below. The raw materials, reagents or devices used in the following examples and comparative examples, unless otherwise specified, can all be obtained from conventional commercial sources, or can be obtained by existing known methods.
[0055] It should be noted that the specific information of some raw materials used in the examples and comparative examples of the present invention are as follows:
[0056] Water-based acrylic resin D: number average molecular weight is 3000 g / mol, hydroxyl value is 95 mgKOH / g, brand is Qingtian R1385;
[0057] Partially methylated amino resin: brand name is allnex cymel 325;
[0058] Matt powder A: unsurface treated silica, brand 560N;
[0059] Matt powder OK412: surface treated with silica;
[0060] Matt powder C803: surface treated with silica;
[0061] Aqueous dispersant B: non-ionic dispersant, brand SN-1729;
[0062] Aqueous dispersant 32500: hyperdispersant, purchased from Lubrizol;
[0063] Leveling agent C: polyether modified silicone, brand SN-4341;
[0064] Leveling agent EFKA3772: fluorocarbon modified acrylate;
[0065] Wetting agent: brand Tego 4100;
[0066] Defoaming agent: brand Tego 825;
[0067] Adhesion promoter: brand name is Changxing 4901-B-72;
[0068] Amine neutralizer: N,N-dimethylethanolamine;
[0069] Film-forming cosolvent: ethylene glycol butyl ether;
[0070] Film-forming solvent: diethylene glycol butyl ether.
[0071] Examples 1 to 5 and Comparative Examples 1 to 8
[0072] Examples 1 to 5 and Comparative Examples 1 to 8 each provide a water-based varnish, the specific components are shown in Table 1 and Table 2, and the specific preparation method is as follows:
[0073] The other components except deionized water are blended, and then dispersed at a high speed of 1000-1500 r / min for 25-30 minutes. After the fineness is detected to be ≤15 μm, deionized water is added, and then mixed at a low speed of 500-800 r / min for 5-10 minutes to obtain the water-based varnish.
[0074] Table 1 Components and amounts of Examples 1 to 5 and Comparative Examples 1 to 4 (parts by mass)
[0075]
[0076]
[0077] Table 2 Components and dosages of Comparative Examples 5 to 8 (parts by mass)
[0078]
[0079] Performance Testing
[0080] The water-based varnish of Examples 1 to 5 and Comparative Examples 1 to 8 was sprayed to form a board, and the specific steps were as follows:
[0081] First, the water-based varnish of Examples 1 to 5 and Comparative Examples 1 to 8 was diluted to 25 seconds for spraying, and then sprayed on the black powder coating base plate. The dry film was controlled between 12 and 15 μm, and then baked and cured at 150 degrees for 20 minutes. After cooling for 1 hour, the following performance tests were performed:
[0082] Adhesion: measured according to GB / T 9286-2021; Grade 0 is qualified;
[0083] Hardness: Determined according to GB / T 6739-2022; 2H is qualified;
[0084] Impact performance: measured according to GB / T 1732-2020; 50kg·cm is qualified;
[0085] Transparency: measured according to GB / T 9754-2007; the ratio of glossiness at 20° angle to glossiness at 60° angle is compared. The larger the ratio, the higher the transparency.
[0086] Dilution ratio: 100 parts of varnish is diluted with water to a viscosity value of 2 cups for 25 seconds. The ratio of the weight before dilution to the weight of pure water required for dilution.
[0087] The performance test results are shown in Table 3.
[0088] Table 3 Performance test results of Examples 1 to 5 and Comparative Examples 1 to 8
[0089]
[0090] As can be seen from Table 3, from Examples 1 to 5 and Comparative Examples 1 to 4, it can be seen that the ratio of the gloss at an angle of 20° to the gloss at an angle of 60° (A / B value) of Examples 1 to 5 is ≥ 0.3, while the A / B values of Comparative Examples 1 to 4 are between 0.20 and 0.25, which are all smaller than Examples 1 to 5. It can be seen that Examples 1 to 5 have better transparency effects. It can also be seen from the visual inspection results of the appearance that Examples 1 to 5 have better transparency effects.
[0091] No leveling agent was added in Comparative Examples 1 to 2, and a polymer hyperdispersant was used. The polymer hyperdispersant has a good effect on pigment dispersion, so relatively speaking, it will obtain higher gloss and stability than other types of dispersants. However, improving the gloss is contrary to matte coatings and is obviously not in line with the formulation design principles. The aqueous non-ionic dispersant used in Examples 1 to 5 of the present invention contains a pigment affinity group polymer and a surfactant (mainly polyethylene glycol-type polyols and polyethyleneimine derivatives, etc.), which can reduce surface tension, has strong adsorption, can make the matte powder oriented, and can relatively reduce the gloss of the coating after addition.
[0092] Comparative Examples 3 to 4 did not add dispersant, and used fluorocarbon modified acrylate leveling agent. Fluorocarbon modified silicone has strong anti-shrinkage ability, good thermal stability, and can promote leveling; it has good help for the feel of the coating and the wetting of the substrate, but it does not play a big role in the change of the gloss of the coating. Examples 1 to 5 of the present invention use polyether modified silicone leveling agent. The silicone leveling agent modified by polyether improves the compatibility with the resin, reduces the surface tension and controls the surface flow. The effect is very good, and the use of polyether modified silicone can reduce the gloss of the coating by 30-40% under the condition of the same amount of matte powder added. Moreover, non-ionic dispersants can also reduce the gloss of the coating more than polymer dispersants, which means that after adding polyether modified silicone and non-ionic wetting dispersants, the combination of the two can effectively reduce the amount of matte powder in the formula, thereby improving the permeability of the coating.
[0093] Moreover, the surface-treated silica used in Comparative Examples 1 to 4 is better in hand feel and better in suspension, but not conducive to dispersion in an aqueous system; while the untreated matte powder is more cost-effective, has better wettability in an aqueous system, and has higher transparency after film formation. The matte powder added in Examples 1 to 5 of the present invention is not surface-treated, which can be better mixed with the aqueous non-ionic dispersant of the present invention during the preparation of the aqueous varnish to achieve a better dispersion effect.
[0094] It can be seen from Examples 1 to 5 and Comparative Examples 5 to 8 that when other components and dosages are the same and only the number average molecular weight or hydroxyl value of the waterborne acrylic resin is changed, Comparative Example 5 uses a waterborne acrylic resin with a number average molecular weight of 900. The result after curing is: A / B value>0.30, but its 60° angle gloss>50GU, the gloss is relatively high, so more matting powder needs to be added, and the A / B value will also decrease after the gloss decreases, which will lead to increased costs; and because the resin molecular weight is low, the dilution ratio is very low, which will increase the cost of paint and make it easy to sag. Comparative Example 6 uses a waterborne acrylic resin with a number average molecular weight of 4000. The result after curing is: the dilution ratio is very high, resulting in low construction solid content, severe glossiness, and poor fullness. Comparative Example 7 uses a waterborne acrylic resin with a hydroxyl value of 65mgKOH / g. The result after curing is: the adhesion is significantly reduced, not as good as the adhesion of the embodiment, and the A / B value is less than 0.3, and the permeability is reduced. Comparative Example 8 uses a water-based acrylic resin with a hydroxyl value of 120 mgKOH / g. The result after curing is: a high dilution ratio and high gloss, which is difficult to matte and increases the cost required for matte.
[0095] In summary, the present invention adopts a water-based acrylic resin with a specific molecular weight and hydroxyl value, combined with an amino resin, and adopts a non-ionic dispersant to disperse the unsurface-treated silica matte powder, and adds a polyether-modified silicone leveling agent to obtain a highly permeable semi-matte water-based varnish, which solves the problems of fogging, whitishness and opacity of water-based varnish, and has a wide range of applications in building material coating, furniture coating or interior decoration, especially on the thermal transfer coating of iron doors, and can obtain a good permeability effect.
Claims
1. A water-based varnish, characterized in that: The invention comprises the following components in parts by weight: 35-50 parts of water-based acrylic resin, 10-20 parts of amino resin, 1-3 parts of matte powder, 0.5-2 parts of water-based nonionic dispersant, 0.1-1 parts of polyether-modified organic silicon leveling agent, 10-25 parts of auxiliary agent, and 10-30 parts of water; The number average molecular weight of the waterborne acrylic resin is 1500-3500 g / mol; the hydroxyl value of the waterborne acrylic resin is 80-110 mgKOH / g; and the matte powder is selected from unsurface-treated silicon dioxide.
2. The water-based varnish according to claim 1, characterized in that The amino resin is selected from partially methylated amino resins; The etherification degree of the partially methylated amino resin is 40-60%.
3. The water-based varnish according to claim 1, characterized in that: The aqueous nonionic dispersant includes polyethylene glycol type polyol, polyethyleneimine compound or a combination thereof.
4. The water-based varnish according to claim 1, characterized in that: The polyether-modified silicone leveling agent includes ethylene oxide polyether-modified silicone, propylene oxide polyether-modified silicone or a combination thereof.
5. The water-based varnish according to claim 1, characterized in that: The auxiliary agent includes at least one of an amine neutralizer, a film-forming cosolvent, a wetting agent, a defoamer or an adhesion promoter.
6. The water-based varnish according to claim 1, characterized in that: In parts by mass, the auxiliary agent includes: 1 to 3 parts of an amine neutralizer, 10 to 20 parts of a film-forming cosolvent, 0.1 to 1 part of a wetting agent, 0.1 to 1 part of a defoaming agent, and 0.1 to 1.5 parts of an adhesion promoter.
7. The water-based varnish according to claim 5 or 6, characterized in that: The amine neutralizer includes at least one of aqueous ammonia, N,N-dimethylethanolamine, triethylamine or triethanolamine; And / or, the film-forming cosolvent includes at least one of ethylene glycol butyl ether, propylene glycol methyl ether or diethylene glycol butyl ether; and / or, the wetting agent comprises at least one of an acetylenic glycol compound, a modified polysiloxane, a nonionic surfactant or a fluorine-containing surfactant; and / or, the defoaming agent comprises at least one of polydimethylsiloxane, mineral oil or acrylate defoaming agent; And / or, the adhesion promoter includes at least one of an epoxy phosphate adhesive, a titanate adhesive or a polymer polyester adhesive.
8. A method for preparing a water-based varnish according to any one of claims 1 to 7, characterized in that: The following steps are involved: The water-based acrylic resin, amino resin, matte powder, water-based nonionic dispersant, polyether-modified organic silicon leveling agent and auxiliary agent are blended and dispersed at high speed, and finally water is added and mixed at low speed to obtain the water-based varnish.
9. A coating, characterized in that: It is made from the water-based varnish according to any one of claims 1 to 7; preferably, the coating has a 60° angle gloss of 30 to 50 GU; preferably, the coating is a thermal transfer coating for iron doors.
10. Use of the water-based varnish according to any one of claims 1 to 7 in building material coating, furniture coating or interior decoration.
Citation Information
Patent Citations
Water-based aluminum powder stoving varnish capable of being cured at low temperature as well as preparation method and application of water-based aluminum powder stoving varnish
CN114410162A